Reducing dentine hypersensitivity with nano-hydroxyapatite toothpaste: a double-blind randomized controlled trial - Vano, M.; Derchi, G.; Barone, A.; Pinna, R.; Usai, P.; Covani, U (Clinical oral investigations, 2018)
Objectives The present randomized double-blind clinical trial aimed to compare the efficacy in reducing dentin hypersensitivity of a dentifrice formulation containing nano-hydroxyapatite with a fluoride dentifrice and a placebo. Methods and materials One hundred and five subjects were recruited to participate in the study. A computer-generated random table with blocking to one of the three study treatments was used in order to have 35 subjects per group: (1) nano-hydroxyapatite 2% gel toothpaste fluoride free; (2) fluoride gel toothpaste; (3) placebo. Groups 1, 2, and 3 were instructed to treat their teeth for 10 min twice a day with the provided toothpaste gel. The participant’s dentin hypersensitivity was evaluated at baseline and after 2 and 4 weeks using airblast and tactile tests. In addition, a subjective evaluation using a visual analogue scale was used. Results Significant lower values of cold air sensitivity and tactile sensitivity ( p < 0.05) were found for the test group at 2 weeks and 4 weeks. In addition, statistically significant ( p < 0.05) lower values of sensitivity were reported for group 1 compared to those for groups 2 and 3 at 2 and 4 weeks, respectively. The VAS scores were significantly lower ( p < 0.05) in the test group at 2 and 4 weeks compared to those at baseline and in the control groups. Conclusion The application of nano-hydroxyapatite in gel toothpaste fluoride free is an effective desensitizing agent providing relief from symptoms after 2 and 4 weeks.